2018
DOI: 10.2196/11192
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Attitudes and Perceptions Regarding the Use of Mobile Health Technologies for Living Kidney Donor Follow-Up: Survey Study

Abstract: BackgroundIn 2013, the Organ Procurement and Transplantation Network began requiring transplant centers in the United States to collect and report postdonation living kidney donor follow-up data at 6 months, 1 year, and 2 years. Despite this requirement, <50% of transplant centers have been able to collect and report the required data. Previous work identified a number of barriers to living kidney donor follow-up, including logistical and administrative barriers for transplant centers and cost and functional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…In formative research conducted at the Johns Hopkins Hospital, 95 of 100 LKDs reported owning a smartphone [31], which is consistent with Pew Research Center findings that 92% of adults in the United States owned a mobile phone in 2015 [32]. Among participants, 80% (80/100) thought that mHealth technology would be useful in completing follow-up [31].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In formative research conducted at the Johns Hopkins Hospital, 95 of 100 LKDs reported owning a smartphone [31], which is consistent with Pew Research Center findings that 92% of adults in the United States owned a mobile phone in 2015 [32]. Among participants, 80% (80/100) thought that mHealth technology would be useful in completing follow-up [31].…”
Section: Introductionmentioning
confidence: 59%
“…In formative research conducted at the Johns Hopkins Hospital, 95 of 100 LKDs reported owning a smartphone [31], which is consistent with Pew Research Center findings that 92% of adults in the United States owned a mobile phone in 2015 [32]. Among participants, 80% (80/100) thought that mHealth technology would be useful in completing follow-up [31]. A pilot study of 69 LKDs found that engagement through short message service (SMS) text messages exceeded 80% at 2 years postdonation, compared with only 20% using traditional follow-up engagement strategies (ie, telephone; electronic medical record, EMR; or patient portal).…”
Section: Introductionmentioning
confidence: 99%
“…surveyed at a single transplant center perceived mHealth for LKD follow-up as useful, and 79% of participants perceived accessing LKD information and resources on their smartphone as useful 29. These studies show that LKDs are willing to engage with mHealth technology, and use of mHealth for LKD follow-up would be feasible in this population if transplant centers were to design and implement mHealth systems.…”
mentioning
confidence: 79%
“…This has been shown to increase engagement and willingness among living donors. 16 An interesting finding of our survey was the awareness of social media's educational role among medical professions. Of survey respondents, 61% who were working in academic institutions connected through their mobile applications multiple times per day during scientific meetings.…”
Section: Social Media Benefitsmentioning
confidence: 91%